First field evidence infection of Culex perexiguus by West Nile virus in Sahara Oasis of Algeria - S Benbetka; A Hachid; K E Benallal; C Benbetka; A Khaldi; I Bitam; Z Harrat (Journal of Vector Borne Diseases, 2018)
Background & objectives: West Nile virus (WNV) is considered one of the most widely distributed arboviruses in the world which is transmitted by several mosquito species including the Culex genus. Culex pipiens is the major vector of this virus in Europe and USA whereas in African countries, other species such as Cx. perexiguus is considered as an important vector. This paper aimed to study the mosquito species involved in WNV transmission in Aougrout, one of the highly populated Oasis of Timimoun Province in Algeria where human WNV neuroinvasive diseases are prevalent. Methods: CDC light-traps were installed in animal and human shelters for three nights. Collected mosquitoes were pooled and real-time PCR was performed to detect and identify WNV lineages 1 and 2 in the samples. Results: CDC light-traps collected 270 mosquitoes belonging to three genera. Culex genus was predominant with Cx. perexiguus as main species followed by Aedes and Anopheles genus. A total of 33 pools were tested; one pool containing Cx. perexiguus was found positive for WNV lineage 1. Interpretation & conclusion: This study reports for the first time a WNV natural infection of Culex perexiguus in the study region indicating that species other than Cx. pipiens should be taken into consideration in WNV surveillance, especially in specific environments like Saharan Oasis ecosystem.